2018
DOI: 10.1371/journal.pone.0199813
|View full text |Cite
|
Sign up to set email alerts
|

Gaming behaviour with Pokémon GO and physical activity: A preliminary study with medical students in Thailand

Abstract: Pokémon GO becomes the most rapidly downloaded mobile application in history. This study aimed to determine the physical activity of medical students, who played Pokémon GO, and the change in their use of Pokémon GO and physical activity over time. An observational study was conducted. Physical activity was measured by using self-administered questionnaires at baseline (phase 0), 1 month (phase 1) and 3 months (phase 2) post-Pokémon GO download. The changes in physical activity (phase 0 to 1 and phase 1 to 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…it utilized self-report surveys of physical activity and revealed that 57.7% of the participants had stopped playing the game after 3 months. it was observed that players utilized the application for fun or as a pastime rather than for fitness purposes [27]. Another study findings were consistent with this in that the players' step intake increased for the first 5 weeks after downloading the application, and then returned to pre-installation levels [12].…”
Section: Discussionsupporting
confidence: 60%
“…it utilized self-report surveys of physical activity and revealed that 57.7% of the participants had stopped playing the game after 3 months. it was observed that players utilized the application for fun or as a pastime rather than for fitness purposes [27]. Another study findings were consistent with this in that the players' step intake increased for the first 5 weeks after downloading the application, and then returned to pre-installation levels [12].…”
Section: Discussionsupporting
confidence: 60%
“…Prolonged playing of video games increases the risk of repetitive strain injuries, seizures among persons with epilepsy or photosensitivity, injuries due to distractions from the real world (eg, injuries incurred while using mobile devices), and criminal incidents (eg, injuries incurred while playing games in a dangerous or inappropriate place). [12][13][14] On the professional level, eSports may lead to work-related illnesses, such as occupational overuse syndrome due to repetitive movements, overuse of muscles and inappropriate postures, and computer vision syndrome or video game vision syndrome. 15,16 The public health sector should focus on injury prevention, safety issues, and occupational health of eSports athletes and spectators.…”
Section: Video Game-related Illnesses and Injuriesmentioning
confidence: 99%
“…In this case, only the parent article was included. Finally, 36 articles [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] were included for this review.…”
Section: Resultsmentioning
confidence: 99%
“…In these articles, the indicators of PA included daily step counts, time spent and/or distance travelled in various activities (i.e., walking, biking, running/jogging, and skating), time spent in sedentary, light, moderate-to-vigorous, vigorous PA, energy expenditure, and exercise frequency. In 14 studies [ 25 , 26 , 29 , 32 , 34 , 36 , 38 , 40 , 43 , 45 , 47 , 50 , 52 , 53 ], PA was assessed solely with subjective measures such as the International Physical Activity Questionnaire. Eight studies [ 21 , 24 , 28 , 30 , 33 , 35 , 39 , 41 ], incorporated only objective measures to assess participants’ PA such as pedometers, accelerometers, wrist or arm-worn activity sensors, heart rate monitors, and mobile applications, such as the iPhone Health app, step-counting app, and ecological momentary assessment app.…”
Section: Resultsmentioning
confidence: 99%